2020
DOI: 10.3390/agronomy10060794
|View full text |Cite
|
Sign up to set email alerts
|

Facing Climate Change: Application of Microbial Biostimulants to Mitigate Stress in Horticultural Crops

Abstract: In the current scenario of rapidly evolving climate change, crop plants are more frequently subjected to stresses of both abiotic and biotic origin, including exposure to unpredictable and extreme climatic events, changes in plant physiology, growing season and phytosanitary hazard, and increased losses up to 30% and 50% in global agricultural productions. Plants coevolved with microbial symbionts, which are involved in major functions both at the ecosystem and plant level. The use of microbial biostimulants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 196 publications
0
87
0
1
Order By: Relevance
“…However, the complexity and speci city of the patterns described in this work suggests that the idea to replace agro-chemicals by a few universal bene cial microorganisms is not realistic. Therefore, breeding programs should aim at the selection of high quality, climate-change resilient horticultural varieties with remarkable capacity to establish symbiotic relationships with useful microorganisms 8 . The inclusion of microbial markers in marker-assisted selection will represent a paradigm shift in plant breeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the complexity and speci city of the patterns described in this work suggests that the idea to replace agro-chemicals by a few universal bene cial microorganisms is not realistic. Therefore, breeding programs should aim at the selection of high quality, climate-change resilient horticultural varieties with remarkable capacity to establish symbiotic relationships with useful microorganisms 8 . The inclusion of microbial markers in marker-assisted selection will represent a paradigm shift in plant breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several bacterial species present the 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity. ACC deaminase degrades the ethylene precursor, thus, impairing its production in the plant tissues 8 .…”
Section: Interactions Between Strawberry Microbiome Plant Mineral Comentioning
confidence: 99%
See 2 more Smart Citations
“…The rhizobia-colonized lima bean plants showed that indole represents the agent of the repellent effects at jasmonic acid (JA)-induced VOCs [17]. PGPR, free-living root-associated bacteria, have been studied since the last century with the aim to increase plant growth and productivity [21,22]. Studies show that PGPR promote plant growth via bacterial determinants that induce the production and phosphate dissolution of plant hormones such as indole 3-acetic acid, gibberellic acid, JA, SA, and cytokinin [23][24][25].…”
Section: Introductionmentioning
confidence: 99%